Housing and the money market - Starr, Roger (New York : Basic Books, 1975)
Fundamentals of housing, the lending institutions in mortgage, governmental institutions and future of policy.
Includes bibliographical references and index.
sju 22/01/2019
Loans
Keywords: Housing